Case Refusal: A Right for the Public Defender But Not a Remedy for the Defendant - John P. Gross (Washington University Law Review, 2017)
Various arguments have been made to explain why public defenders continue to handle excessive caseloads: a lack of independence, organizational culture, or ethical blindness among them. All of these arguments are based on the idea that a public defender elects to labor under an excessive caseload either because they do not see it as excessive or because they realize it is but believe a refusal will lead to adverse consequences for themselves. In this essay, I argue that the decision to maintain an excessive caseload may not always be attributable to self- interest on the part of the public defender, but can be motivated by a concern for the welfare of prospective clients. The possibility that case refusal will result in prospective clients receiving no representation, the poor quality of alternative counsel, and the lack of any meaningful remedy for defendants who are denied representation creates a situation where representation by a public defender with an excessive caseload can be seen as the defendant’s best option.
Keywords: public defender; case refusal; right to representation